Efficacy, Chemical Constituents, and Pharmacological Actions of Radix Paeoniae Rubra and Radix Paeoniae Alba - Tan, Yu-Qing; Chen, Heng-Wen; Li, Jun; Wu, Qing-Juan (Frontiers in Pharmacology, 2020)
Radix Paeoniae Rubra and Radix Paeoniae Alba are the different characteristic forms of Paeonia lactiflora Pall. They are widely used as traditional Chinese medicines in clinical practices. This study analyzes the development history, efficacy, chemical compositions and pharmacological effects of Radix Paeoniae Rubra and Radix Paeoniae Alba, and explores the causes of the similarities and differences of these two amalgams. It provides a basis for the clinical application of these two Chinese medicinal materials, and lays a foundation for further study of the pharmacological effects and the quality identification of Paeonia lactiflora Pall as it applies to traditional Chinese medicine.